Analyzing the impact of branding factors (image, equity, and trust) on coffee purchase decisions - Ngiu, Abdul Fattah; Aprileny, Imelda (Sekolah Tinggi Ilmu Ekonomi Indonesia Jakarta, 2025)
This study examines the influence of brand image, brand equity, and brand trust on coffee purchasing decisions, using a branch of a notable coffee shop chain in Jakarta as a case study. A quantitative survey method was employed, with data collected via an online questionnaire distributed via Google Forms and analyzed using partial least squares structural equation modeling (PLS-SEM) with SmartPLS 3.9. The findings indicate that brand image, brand equity, and brand trust each have a significant positive impact on customer purchase decisions. Notably, brand trust was identified as the dominant factor influencing purchasing behavior. Practically, the results provide a clear strategic directive for coffee shop managers: while investments in brand image and brand equity are necessary, prioritizing initiatives that build and solidify brand trust—such as ensuring unwavering product consistency, fostering transparent customer communication, and reliably fulfilling service promises—will be the most effective pathway to securing and increasing purchase decisions